Effectiveness of Dialectical Behavior Therapy–Informed Family Therapy on Family Functioning and Emotion Regulation in Adolescents with Emotional Dysregulation - Yousefpour, Nahid (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study investigated the effectiveness of DBT-informed family therapy on family functioning and emotion regulation in adolescents with emotional dysregulation in Tabriz, Iran.Methods and Materials: A quasi-experimental pretest–posttest design with control group and 3-month follow-up was used. Participants were 40 adolescents (aged 13–18 years) with clinically significant emotional dysregulation, referred to outpatient counseling centers in Tabriz, and one or both of their parents. Eligible families were selected through purposive sampling and then randomly assigned to intervention (n = 20) or wait-list control (n = 20) groups. The intervention group received 10 weekly DBT-informed family therapy sessions focusing on mindfulness, distress tolerance, emotion regulation, interpersonal effectiveness, and validation within family interactions. All participants completed standardized measures of family functioning and emotion regulation at baseline, post-treatment, and follow-up. Data were analyzed using repeated-measures ANOVA and effect size indices.Findings: Families in the intervention group showed significantly greater improvement in overall family functioning and adolescent emotion regulation compared to the control group at post-test. These gains were largely maintained at 3-month follow-up.Conclusion: DBT-informed family therapy appears to be an effective approach for improving family functioning and emotion regulation among adolescents with emotional dysregulation in Tabriz. Integrating DBT principles into family-based interventions may enhance culturally sensitive clinical practice in Iranian adolescent mental health services.